A Novel Clonal Selection Algorithm for Multivariable Optimal Control of Activated Sludge Process - Du, X.J.; Hao, X.H.; Yu, P.; Gu, Q.; Li, H.J. (Asian Journal of Chemistry, 2012)
A novel clonal selection algorithm (NSCA) was proposed in this work and we introduced the novel clonal selection algorithm into the wastewater treatment activated sludge process for multivariable optimal control with the lowest operational costs by limiting total substrate discharge mass. A simulation results shows that the new method is efficient and also provides a new approach for other optimal control problem.